Mechanochemical synthesis, characterization and thermoanalytical study of a new curcumin derivative - de Moura, Aniele [UNESP]; Gaglieri, Caroline [UNESP]; da Silva-Filho, Luiz Carlos [UNESP]; Caires, Flávio Junior [UNESP] (Springer Nature, 2020)
The curcumin is the major constituent of turmeric plant (Curcuma longa), which presents several biological activities such as antioxidant, bactericidal, anti-inflammatory and antitumor. An interesting strategy to improve its properties is to synthetize curcumin derivatives. Thus, the synthesis of a new curcumin derivative (DCUR) with 4-carboxybenzaldehyde (4-CBA) becomes interesting, which occurs by a Knoevenagel reaction, a common methodology used to synthesize curcumin analogues. The synthesis was carried out by the mechanochemical method, which is an efficient green method for the synthesis of organic compounds. The most efficient grinding time for mechanochemical synthesis was determined using PXRD and DSC techniques. 1H NMR, DEPTQ and FTIR analyses confirmed the structure of DCUR. This new methodology is more efficient (at least 5×), and cleaner than usual methods described in the literature to obtain a new compound by Knoevenagel reaction. The TG–DTA, DSC and DSC-microscopy techniques were used to confirm the formation of the compound and to study its thermal behavior. Moreover, the thermoanalytical of 4-CBA showed that this compound presents a reversible solid–solid phase transition.
Keywords: 4-Carboxybenzaldehyde; Curcuminoids; Knoevenagel reaction; Mechanochemistry; Solid–solid phase transition; Thermal analysis